2014
DOI: 10.1016/j.ijgo.2014.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a pilot program to implement physical therapy for women with gynecologic fistula in the Democratic Republic of Congo

Abstract: Pelvic floor physical therapy could have significant results in women with gynecologic fistula, may be an important adjunctive treatment in comprehensive fistula care, and warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…Outcomes from two interventions combining health education and physiotherapy were not directly comparable . At hospital discharge, Castille et al.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Outcomes from two interventions combining health education and physiotherapy were not directly comparable . At hospital discharge, Castille et al.…”
Section: Resultsmentioning
confidence: 97%
“…Two studies tested a combined health education and physiotherapy program . In Benin, Castille et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has indicated that there can be an improved outcome of surgery both in terms of successful closure of a vesicovaginal fistula and reduced risk of persistent urinary incontinence if women are taught a correct pelvic floor muscle (PFM) contraction and advised to practice pelvic floor muscle exercises (PFME). Other researchers have recommended pre‐operative assessment although most of their study population were first seen following fistula repair.…”
Section: Pelvic Floor Physiotherapymentioning
confidence: 99%